THE NOTARY’S AUTHORITY IN ENSURING THE VALIDITY OF INTERNASIONAL CONTRACTS WITH A CHOICE OF LAW - Armiandi, Nur Hikmah (JILPR Journal Indonesia Law and Policy Review, 2025)
Globalization has increased cross-border business interactions, resulting in international business contracts involving multiple jurisdictions and legal systems. A critical clause in these contracts is the choice of law or the selection of foreign law. This article aims to analyze the authority of notaries in ensuring the validity of international business contracts involving foreign law under Indonesian law. The method used is normative juridical with statutory and conceptual approaches. The study finds that notaries have attributed authority to draft authentic deeds, provide legal counseling, and ensure that contract clauses comply with national legal principles. Notary involvement plays a preventive role in minimizing disputes by aligning contract contents with public policy. Therefore, the notary’s preventive role is essential in ensuring legal certainty for parties engaging in cross-jurisdictional agreements.